The Differential Pattern in Skeletal-Dental Age and Duration of Growth Spurt based on Chronological Age and Gender Types (A Comparison Study Between Indonesian and Malaysian Children Populations) - Seno Pradopo; Sindy Cornelia Nelwan; Ardianti Maartrina Dewi; Amalia Wimarizky; Achmad Nadian Permana; Diana Md Zahid; Syiral Mastura Abdullah (Institute of Medico-legal Publications Pvt Ltd, 2022)
Context: Growth and development is a continuous process that occurs intrauterine and continues until adulthood. In the process of reaching adulthood, children must go through various stages of growth and development, Growth is influenced by two main factors, namely internal (genetic) factors and external (environmental) factors. Internal factors include gender, obstetrics and race or ethnicity. Based on the background pattern above, the researcher wants to compare the difference in the duration of growth spurt between the Malaysian and Indonesian populations in terms of the Cervical Vertebrae Maturation (CVM) seen on the lateral cefalogramAims: to compare the differences in the duration of growth spurt between girl and boy in Indonesian and Malaysia Population based on Cervical Vertebrae Maturation (CVM) seen in the lateral cephalogram to determine the right time and orthodontic treatment plan in order to get maximum treatment results.Methods and Material: The study was conducted in June 2020. The research variables were divided into 3 types, namely independent variables (chronological age), dependent variables (skeletal age and growth spurt duration) and controlled variables (Indonesian population children, Gender, CVM CS3 - CS4). Every sample that met the criteria was performed skeletal maturity analysis using Cervical Vertebrae Maturation.Results: The boy sample required a duration of age to reach maturity, 17.93 months in Indonesia and 17.91 months in Malaysia. Meanwhile, the girs sample only required the duration of growth spurt, namely 6.59 months in Indonesia and 6.64 months in MalaysiaConclusion: There is no significant difference between the duration of growth spurt in Indonesian Boy and Malaysian Boy and so does the duration of growth spurt for Indonesian and Malaysian girl.